Avoiding Bending in Case of Uniaxial Tension with Electromagnetic Forming - Demir, O. K.; Weddeling, C.; Ben Khalifa, N.; Tekkaya, A. E. (Technische Universität Dortmund, 2014)
During electromagnetic forming, excessive bending of the specimen takes place due to high velocities and inertia. We show that the excessive bending can be prevented by optimizing the coil geometry in case of uniaxial tension. The process is simulated with various coil geometries, and the resulting amount of bending is compared to the case of standard Nakajima Test. The comparison shows that the bending can be minimised to acceptable levels to be able to call the method a decent way of determining forming limits. The results should be verified experimentally.
Keywords: Forming limits; Nakajima Test; Electromagnetic forming; 620; 670